How to avoid black markets for appointments with online booking systems - Rustamdjan Hakimov; Christian-Philipp Heller; Dorothea Kübler; Morimitsu Kurino (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Allocating appointment slots is presented as a new application for market design. We consider online booking systems that are commonly used by public authorities to allocate appointments for driver's licenses, visa interviews, passport renewals, etc. We document that black markets for appointments have developed in many parts of the world. Scalpers book the appointments that are offered for free and sell the slots to appointment seekers. We model the existing first-come-first-served booking system and propose an alternative system. The alternative system collects applications for slots for a certain time period and then randomly allocates slots to applicants. We investigate the two systems under conditions of low and high demand for slots. The theory predicts and lab experiments confirm that scalpers profitably book and sell slots under the current system with high demand, but that they are not active in the proposed new system under both demand conditions.
Keywords: C92; D47; 330; market design; online booking system; first come first served; scalping